On $[p, q]$-Order of Solutions of Higher Order Complex Linear Differential Equations in an Angular Domain of Unit Disc (Journal of Mathematical Study, 2017)
We study the growth of solutions of higher order complex linear differentialequations in an angular domain of the unit disc instead of the whole unit disc. Someestimations of $[p,q]$-order of solutions of the higher order differential equations in anangular domain are found in this paper.
Keywords: Complex differential equation; analytic function; $[p; q]$-order; angular domain; unit disc.